Hyperarousal and sleep reactivity in insomnia: current insights - Kalmbach DA (Dove Medical Press, 2018)
David A Kalmbach,1 Andrea S Cuamatzi-Castelan,1 Christine V Tonnu,1 Kieulinh Michelle Tran,1 Jason R Anderson,2 Thomas Roth,1 Christopher L Drake1 1Thomas Roth Sleep Disorders and Research Center, Henry Ford Health System, Detroit, MI, USA; 2Department of Psychological Sciences, Kent State University, Kent, OH, USA Abstract: Hyperarousal is a key component in all modern etiological models of insomnia disorder. Overall patterns in the literature suggest that over-active neurobiological and psychological systems contribute to difficulty sleeping. Even so, mixed results regarding the specific mechanisms linking hyperarousal to sleep disturbance limit current etiological conceptualizations. Similar basal arousal profiles between individuals with high vs low risk for insomnia in the absence of stress exposure suggest that dysregulated stress “response” rather than general hyperarousal may be a more pertinent marker of risk. In this report, we discuss evidence for hyperarousal in insomnia and explore the role of sleep reactivity. A trait characteristic, sleep reactivity is the degree to which stress disrupts sleep, manifesting as difficulty falling and staying asleep. Premorbid sleep reactivity has been shown to identify individuals at risk for future insomnia disorder, such as highly reactive sleepers (whose sleep systems are sensitive to stress) who are at elevated disease risk. Research points to genetics, family history of insomnia, gender, and environmental stress as factors that influence sleep reactivity. Importantly, stress-related cognitive–emotional reactivity (e.g., rumination, worry) may exploit the vulnerability of a highly reactive sleep system. We propose that sleep reactivity and cognitive–emotional reactivity may share a bidirectional relationship, conferring an insalubrious environment for sleep in response to stress. Future research on sleep reactivity is needed to identify its neurobiology, characterize its relationship with cognitive–emotional reactivity, and explore the potential clinical utility of sleep reactivity in treatment planning. Keywords: insomnia, hyperarousal, stress, sleep reactivity